К иконографии фрески храма «Трех всадников» под Эски-Керменом - Степаненко, В.П. (Материалы по археологии, истории и этнографии Таврии, 2003)
Церковь “Трех всадников” под Эски-Керменом высечена в обломке скалы и, судя по размерам, возможно, была погребальным храмом. На ее алтарной стене сохранились остатки фрески с изображением трех святых воинов всадников. Having analyzed the iconography in the church of “Three riders” the author makes an assumption that Saint George is depicted on it in his three hypostases: as a triumpher, dragon fighter and liberator of captives. The fresco is dated back to the mid-13** century. The appearance of such a plot is probably connected with the Tatars’ raids into the South-Western Crimea, when “liberation of captives" became vitally important.